Transcriptome-wide m6A methylome analysis uncovered the changes of m6A modification in oral pre-malignant cells compared with normal oral epithelial cells - Chen, Xun; Chen, Liutao; Tang, Yuquan; He, Yi; Pan, Kuangwu; Yuan, Linyu; Xie, Weihong; Chen, Shangwu; Zhao, Wei; Yu, Dongsheng (Frontiers in Oncology, 2022)
As the most common post-transcriptional RNA modification, m6A methylation extensively regulates the structure and function of RNA. The dynamic and reversible modification of m6A is coordinated by m6A writers and erasers. m6A reader proteins recognize m6A modification on RNA, mediating different downstream biological functions. mRNA m6A modification and its corresponding regulators play an important role in cancers, but its characteristics in the precancerous stage are still unclear. In this study, we used oral precancerous DOK cells as a model to explore the characteristics of transcriptome-wide m6A modification and major m6A regulator expression in the precancerous stage compared with normal oral epithelial cell HOEC and oral cancer cell SCC-9 through MeRIP-seq and RT-PCR. Compared with HOEC cells, we found 1180 hyper-methylated and 1606 hypo-methylated m6A peaks and 354 differentially expressed mRNAs with differential m6A peaks in DOK cells. Although the change of m6A modification in DOK cells was less than that in SCC-9 cells, mRNAs with differential m6A in both cell lines were enriched into many identical GO terms and KEGG pathways. Among the 20 known m6A regulatory genes, FTO, ALKBH5, METTL3 and VIRMA were upregulated or downregulated in DOK cells, and the expression levels of 10 genes such as METTL14/16, FTO and IGF2BP2/3 were significantly changed in SCC-9 cells. Our data suggest that precancerous cells showed, to some extent, changes of m6A modification. Identifying some key m6A targets and corresponding regulators in precancerous stage may provide potential intervention targets for the prevention of cancer development through epigenetic modification in the future.